Gel-forming antagonist provides a lasting effect on CGRP-induced vasodilation - Chang, Chia Lin; Cai, Zheqing; Hsu, Sheau Yu Teddy (Frontiers in Pharmacology, 2022)
Migraine affects ~15% of the adult population, and the standard treatment includes the use of triptans, ergotamines, and analgesics. Recently, CGRP and its receptor, the CLR/RAMP1 receptor complex, have been targeted for migraine treatment due to their critical roles in mediating migraine headaches. The effort has led to the approval of several anti-CGRP antibodies for chronic migraine treatment. However, many patients still suffer continuous struggles with migraine, perhaps due to the limited ability of anti-CGRP therapeutics to fully reduce CGRP levels or reach target cells. An alternative anti-CGRP strategy may help address the medical need of patients who do not respond to existing therapeutics. By serendipity, we have recently found that several chimeric adrenomedullin/adrenomedullin 2 peptides are potent CLR/RAMP receptor antagonists and self-assembles to form liquid gels. Among these analogs, the ADE651 analog, which potently inhibits CLR/RAMP1 receptor signaling, forms gels at a 6-20% level. Screening of ADE651 variants indicated that residues at the junctional region of this chimeric peptide are important for gaining the gel-forming capability. Gel-formation significantly slowed the passage of ADE651 molecules through Centricon filters. Consistently, subcutaneous injection of ADE651 gel in rats led to the sustained presence of ADE651 in circulation for >1 week. In addition, analysis of vascular blood flow in rat hindlimbs showed ADE651 significantly reduces CGRP-induced vasodilation. Because gel-forming antagonists could have direct and sustained access to target cells, ADE651 and related antagonists for CLR/RAMP receptors may represent promising candidates for targeting CGRP- and/or adrenomedullin-mediated headaches in migraine patients.